Estudo de sistemas de európio trivalente aplicados no desenvolvimento de materiais luminescentes - Jesus, Larissa Tavares de (2022)
Systems containing lanthanide ions have attracted great attention from the scientific community due to their wide field of applications, ranging from biomedicine to optical use. The investigation of applications of these structures represents a large area of research, either through experimental or theoretical means, mainly with regard to the luminescent properties, due to the unique characteristics that lanthanides present. Theoretical tools can provide useful information for the understanding of phenomena that are not explained experimentally as well as assist in the design of new systems. In this context, the present work aims to study the luminescent properties of different systems using semi-empirical methodologies, such as the Sparkle models, the INDO/S-CIS method, the Judd-Ofelt theory and the energy transfer models proposed by Malta and contributors. The theories and models used to deal with the spectroscopic properties of these systems are implemented in the computational package LUMPAC – Luminescence Package, which was used in this study. Initially, the evaluation of the prediction capacity of the structures containing the trivalent europium lanthanide ion was carried out, for this, the methods Sparkle/AM1, Sparkle/PM3, Sparkle/PM6, Sparkle/PM7, Sparkle/RM1 and RM1 were used. The results obtained from the optimization calculation of the structures suggested the method that was more accurate to predict the structures evaluated in each study. The intensity parameters (Ω2, Ω4 and Ω6) of the systems were calculated and then the calculation of the transfer and retro-transfer rates of energy was used, as well as the obtainment of the radiative and non-radiative decay rate. The theoretically obtained results were compared with the experimental results, which is a strong indication that the proposed structures were systems corresponding to those that were synthesized, including, in one of the cases, used for structural elucidation and also the possibility of explaining phenomena not observed experimentally.